2011
DOI: 10.1002/eat.20824
|View full text |Cite
|
Sign up to set email alerts
|

College students' perceptions of individuals with anorexia and bulimia nervosa

Abstract: Objective Eating disorders (EDs) are highly stigmatized conditions. The current study explored factors hypothesized to influence this stigmatization including ethnicity, gender, ED subtype, and proposed etiology. Methods Undergraduates (N=235) read scenarios depicting fictional characters varying on ethnicity, gender ED subtype, and etiology. Participants reported perceptions of each character, and completed the EAT-26 and the Level-of-Contact scale. Results Characters with BN were viewed as more responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 30 publications
(59 reference statements)
8
82
1
1
Order By: Relevance
“…Generally the students felt that disordered eating attracted a negative if not stigmatising label (n=9). This would seem to correspond with the literature where Wingfield et al [42] suggest a degree of stigma attaching to university students manifesting disordered eating and might possibly correlate with low treatment seeking evident amongst some students [5].…”
Section: Um Not Really For This Issue As Much It's Not Really Talkedsupporting
confidence: 88%
“…Generally the students felt that disordered eating attracted a negative if not stigmatising label (n=9). This would seem to correspond with the literature where Wingfield et al [42] suggest a degree of stigma attaching to university students manifesting disordered eating and might possibly correlate with low treatment seeking evident amongst some students [5].…”
Section: Um Not Really For This Issue As Much It's Not Really Talkedsupporting
confidence: 88%
“…People with depression or eating disorders are similarly stereotyped as more “competent” (and “warm”) than those with schizophrenia (Sadler et al, 2012), suggesting greater responsibility. As with depression, describing AN in terms of genetics elicited less blame or responsibility (Crisafulli, 2008; 2010; Wingfield, 2011), as well as less perceived triviality, weakness, and selfishness (Crisafulli, 2010), and self-destructiveness (Wingfield, 2011). …”
Section: Genetics and Stigma For Different Psychiatric Diagnosesmentioning
confidence: 99%
“…Recent studies show mental illness stigma is usually exacerbated by biogenetic framing (see reviews by Angermeyer et al, 2011; Read et al, 2006). Yet studies of AN/BN suggest stigma-alleviation with genetic etiology (Crisafulli et al, 2008; 2010; Wingfield et al, 2011), likely because eating disorder stigma centers on personal responsibility, rather than dangerousness or unpredictability (which genetic framing appears to exacerbate; Angermeyer et al, 2011). …”
mentioning
confidence: 99%
“…[6,8,[17][18][19][20][21][22][23][24] Stuart [24] suggests that those living with mental illness are "amongst the most stigmatised groups in society". This perhaps reflects Goffman's [25] earlier work on the damaging effects of stigma particularly in relation to mental illness and the impact on the individual's whole personhood; Eisenburg, et al [10] Wingfield, et al [26] suggest the issues with disordered eating can carry a significant stigma, including amongst the college student population. The British Psychological Society [27] seems to favour the use of the term mental distress rather than mental illness, reflecting a significant proportion of sufferers lacking the coping resources to manage stressors; they suggested that a better approach to mental distress reflects the "overwhelming evidence that it is on a spectrum with normal experience" suggesting psychosocial factors as significantly causative.…”
Section: Introductionmentioning
confidence: 72%
“…Disordered eating whether a form of psychopathol-ogy or reflective of problems in living appears to carry a rather negative label and in some instances stigma. [5,26,35,36] Wingfield et al [26] suggest that amongst university students disordered eating carries a stigma with bulimia nervosa carrying a significant stigmatised image of poor self-control. The authors note the sometimes negative impact of media portrayals in the sense of reinforcing potential stigma, and a sense amongst the general public of the individual's responsibility for their condition.…”
Section: Sense Of Coherencementioning
confidence: 99%